Musical creation through time: Curriculum review in secondary education (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
LOGSE (1990) meant the incorporation of musical creation to the Spanish curriculum. Since then, its presence has been continuous as well as irregular in terms of its approach. The objective of this research lies in analyzing the concept of musical creation established in the curricular concretions of the Autonomous Community of Galicia. Through the content and comparative analysis of three decrees, variations are detected in terms of the degree of procedural detail that they provide to the teacher. A generalized ambiguity in its conceptions is concluded, to the detriment of those teachers less familiar with the pedagogies of musical creation.